PENYULINGAN KULIT MASOI (CINNAMOMUM XANTHONEURON BL) BAGIAN 1 (Distillation of Masoi bark (Cinnamomum xanthoneuron BL.). Part I) PENGARUB CARA DAN WAKTU PENYULINGAN KULIT MASOI (The effect of distilling method and time) - Abdul Hakim Lukman; Bambang Wiyono; Poedji Hestoeti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This paper describes a preliminary experiment on the effect of dilstillation method and time on yield of The methods applied were cohobation and water-steam method with distilling times of 3, 9, 18, 30 and 36 hours, consecutivety. The result shows that the distilling time and method appears to have a highly significant effect on oil yisld and the cohobation methad produces higher oil yield compared with water-steam distillation.